Understanding the relationship between perceived school climate and bullying: A mediator analysis. (3rd April 2019) - Acosta, Joie; Chinman, Matthew; Ebener, Patricia; Malone, Patrick S.; Phillips, Andrea; Wilks, Asa
ABSTRACT: This study assesses how perceptions of school climate and four mediating factors (school connectedness, peer attachment, assertiveness, and empathy) influence reports of bullying behaviors among 2, 834 students in 14 middle schools. Results revealed that students in positive school climates reported experiencing fewer physical, emotional, and cyberbullying behaviors. They also reported greater levels of school connectedness, peer attachment, assertiveness, and empathy, which in turn helped explain the influence of perceived school climate on bullying. In addition, the greater levels of empathy that students reported, the more likely they were to report being bullied. These results highlight the role that perceptions of school climate can play in influencing bullying and underscore the importance of mediating factors as schools work to track and improve school climate.